There is comfort in the colors of the rainbow - the consoling function of environment in nursing - Kitzmüller, Gabriele (Nordisk Tidsskrift for Helseforskning, 2022)
In this essay I will try to illuminate the meaning of consolation in nursing. My point of departure is my experience as a next of kin, following my beloved friend in her last days of life in hospital. With the ward nurses’ permission, we transformed her room into a home. Due to the homely atmosphere in this room, everybody felt calm and comforted despite the serious situation. The sense of security and calmness made us more present for each other and contributed to a dignified farewell. In this essay I reflect on how our physical environment with nature included, can make us feel at home even in the midst of death, whatever our role whether we are a patient, nurse or next of kin.
Keywords: consolation; nursing; hospital room; at-home-ness; nature